The Importance of Learning a Second Language Acquisition started from 5 Years Old - Indah Marliana; Murwati Murwati; Tri Rahayu (STIKes Ibnu Sina Ajibarang, 2024)
The early acquisition of a second language is increasingly acknowledged for its benefits in cognitive development, social skills, and academic performance. This journal explores the importance of beginning second language education at the age of five, focusing on the developmental benefits, effective teaching methods, and long-term outcomes. This journal article aims to enhance the current understanding by offering empirical insights into the experiences and perceptions of parents, teachers, and children concerning early second language learning. Through qualitative data analysis from interviews, observations, and documentation of 22 participants. Consisting of 10 parents, 10 students with an age range of 4-6 years, and 2 teachers at the Bimba Aiueo H. Shibi unit South Jakarta, PAUD Institution. This research was conducted from 10 June 2024 to 13 July 2024. Using qualitative descriptive methods, this research seeks to explain the impact of learning a second language acquisition on children's development.